Relationship between the 2014–2015 Holuhraun eruption and the iron record in the East GRIP snow pit. Issue 1 (1st January 2019) - Du, Zhiheng; Xiao, Cunde; Zhang, Qi; Handley, Mike J.; Mayewski, Paul A.; Li, Chuanjin
ABSTRACT: We conducted a 2 m snow pit study in July 2017 at the East GRIP (Greenland Ice-Core Project; northeastern Greenland) deep ice-coring site. We collected snow samples at intervals of 0.05 m and analyzed their iron (Fe) and rare earth element (REE) concentrations. Pronounced seasonal variations in trace elements were observed during 2012–2017. The results indicated that the dissolved Fe (DFe), total dissolved Fe (TDFe), and total dissolved REEs (TDREEs) largely originated from mineral dust, which peaked in winter to early spring. In particular, the 2014–2015 Holuhraun eruption (31 August 2014 to 27 February 2015) can be clearly observed in the data at a depth of 90–125 cm. This event not only provided abundant acidic material (sulphate), but also released a large amount of DFe. Therefore, these results provide a possible way to use Greenland deep ice core data to construct a much longer history and better understand the relationship between eruptions and the release of iron in future studies.